A Comparative Study on Shear Strength Testing of Single and Multi-layer Interfaces using Large Direct Shear Apparatus - Muluti, Shade (Department of Civil Engineering, 2022)
Geotechnical structures such as composite liner systems in landfills consist of multiple interfaces, which include a broad range of geosynthetics in conjunction with soil, rocks and any other related materials. This results in the introduction of many interface planes into the structure, which can potentially create instability especially along the slope and ultimately result in failure. To date, many laboratories use single interface testing instead of multi-layer interface testing to determine geosynthetic shear design characteristic values that are used in the design of structures such as landfill liners. A topic of discussion remains the preferred interface testing configuration and only a few studies have substantiated and quantified the significance of varying the different interface shear testing configurations. This study, therefore, aimed to evaluate and compare the effects of the use of the two interface test configurations on the shear strength of soil/geosynthetic and geosynthetic/geosynthetic interfaces. Furthermore, it was intended to identify the test configuration that provides the most critical shear strength results, while also understanding the fundamental mechanisms responsible for the shear strength observed. In this study, three geosynthetics were used: geotextile (GTX), geomembrane (GMB) and geosynthetic clay liner (GCL), which generally constitute the critical interface components of a lining system in a modern South African landfill liner. Two soils were utilised as a part of the materials required for the investigation and they were: river sand and red clay. The laboratory tests were conducted under saturated conditions in accordance with the ASTM D5321 and ASTM D6243 standards, using a 305 mm x 305 mm large direct shear box. The tests were carried out over a range of applied normal pressures of 50, 100, 200 and 400 kPa. A constant shear rate of 1.0 mm/min was used in the interface tests that did not involve GCLs or clay specimens and therefore no excess pore pressure was anticipated at the interface. On the other hand, for all other interface tests involving either clay or GCLs samples, a shearing rate of 0.1 mm/min was utilized. The results showed that nonlinear behaviour of the shear stress versus shear displacement responses was exhibited in both the single and multi-layer interface tests, regardless of the normal stress applied. However, it was noted that with an increase in normal stress applied, the deviation in mobilized shear stress between the two test configurations increased, with single interface tests yielding higher shear stress values compared to multi-layer interface tests. In single interface tests, the high shear stresses could be related to the clamping that confined each of the test specimens during shearing to one end of the shear block. On the other hand, only the top and bottom test specimens were clamped in multi-layer interface tests, thus allowing failure to have occurred at the weakest of the available interfaces. Moreover, for single interface tests, peak strengths were generally 9% lower for the range of normal stresses considered, whereas Large Displacement (LD) strengths were generally 24 % lower for the single interface tests, compared to the peak and LD strength values for multi-layer interface tests. This was particularly observed at low normal stresses between 50 and 200 kPa, and it could probably have been caused by the rigid clamping of the geosynthetics which results in some tensile strains in the geosynthetics. In addition, it was observed in multi-layer interface tests that a transfer of shear stresses within the system could have occurred, which could have led to higher overall shear resistance of the composite. As a result, single interface tests yielded a conservative estimate of the peak and LD shear strengths for the tested interfaces compared to multi-layer interface tests. This may be attributed to higher displacement along with the critical interface in single interface tests than in multi-layer interface tests. To allow the investigator to observe the displacement, as well as the possible transfer of shear stresses within the system during the shearing of the various geosynthetics, it was recommended that real-time monitoring of the displacement mobilization should be carried out in multi-layer interface tests during shearing.